Experimental investigation of the free swelling of crushed argillite. Issue 2 (13th May 2013) - Wang, L.; Chanchole, S.; Héripré, E.; Bornert, M.
Abstract : Callovo–Oxfordian argillite is studied in France as a possible host rock for repository of high-level radioactive wastes. A new experimental procedure is proposed to quantify the free swelling of its main constitutive clay phase, which is a key parameter to model the hydromechanical behaviour of this rock. The material was pulverised finely enough to remove any local stress that may prevent the free swelling induced by a change in water content. Powders were observed using an environmental scanning electron microscope and images recorded at various degrees of relative humidity were analysed by digital image correlation techniques to measure swelling strains. The investigation showed that the free swelling is moderate in comparison to other expansive clays (e.g. bentonite MX80). The magnitude of deformation becomes significant at high relative humidity. This swelling is not reversible and residual contraction is found after a wetting/drying cycle. These results confirm and provide a possible interpretation of some macroscopic phenomena.